Perchlorate-induced structural diversity in thiosemicarbazone copper(ii) complexes provides insights to understand the reactivity in acidic and basic media. Issue 15 (21st March 2023) - Gil-García, Rubén; Madariaga, Gotzon; Jiménez-Pérez, Alondra; Herrán-Torres, Ignacio; Gago-González, Adrián; Ugalde, María; Januskaitis, Vaidas; Barrera-García, Joaquín; Insausti, Maite; S. Galletero, María; Borrás, Joaquín; Cuevas, José Vicente; et al.
Abstract : Perchlorate ions induce structural diversity in a thiosemicarbazone copper(ii ) system, whose aqueous chemistry includes desulfurization reactions even at physiological pH values. Abstract : The use of perchlorate ancillary ligands with relatively low coordination ability nicely illustrates a rich structural diversity in thiosemicarbazone copper(ii ) (TSC-Cu(ii )) systems. Five compounds with the formulae [CuL(OH2 )][CuL(OClO3 )] n · n ClO4 ·2 n H2 O (1 ), [CuL(OClO3 )2 ] (2 ), [Cu(HL)(OClO3 )2 (OH2 )] H2 O (3 ), [Cu2 L3 ](ClO4 )·2H2 O (4 ) and [Cu(HL)(NCS)](ClO4 ) (5 ) are studied, where HL = pyridine-2-carbaldehyde thiosemicarbazone. The crystal structures show the presence of polynuclear species in the compounds containing an anionic L − thiosemicarbazone ligand: 1D chains (1 ) and dinuclear (2 and 4 ) arrangements. Meanwhile, complexes with a neutral HL ligand give rise to mononuclear entities (3 and 5 ). The chemical and structural parallelism of these complexes with the analogous TSC–Cu(ii )–nitrate system is discussed. The thiocyanate ligand in compound 5 comes from partial desulfurization of the thiosemicarbazone in acid medium and results in an incommensurate modulated structure. On the other hand, it is proposed that [Cu2 L3 ] + species present in 4 could play a possible role in desulfurization reactions. Experimental evidence and theoretical calculations support a proposed mechanism for the partial desulfurization of preformed TSC-Cu(ii ) entities in basic and physiological media to yield the [CuL(L CN )] (HL CN = pyridine-2-ylmethylene(hydrazine carbonitrile)) and [CuL(SH)2 )] compounds.